White-Collar Crime: Contemporary View - Szaplonczay, Aleksandra (Teisė, 2021)
The article touches upon the problem of white collar criminality and presents a contemporary view of the phenomenon.The concept of white-collar crime, first introduced by Edwin H. Sutherland in 1939, immediately became the driving force behind the discussion undertaken by criminologists and sociologists of that time. Since then, many studies have been conducted in order to answer the question about who actually is a “white collar” – why do respectable, well-situated individuals decide to enter the path of crime? The author contrasts two types of definitions – the subjective white-collar crime definition developed in Anglo-Saxon culture and objective definition of economic crime functioning in Europe. It is significant that the crime of white collars has never really been systematized in the Polish legal system (and most of European legal systems), in contrast to economic types of crime.The author compares recent literature, presents characteristics of white-collar criminals and comes to the conclusion that in this specific group of criminals the ties between the perpetrator and the community in which they live are very weak.Finally, the article touches on a problem of possible beneficial consequences of attempting to investigate the scale of crimes committed by white collars.
Keywords: criminality; economic crime; criminal behavior; white-collar crime; criminal law